2018
DOI: 10.1038/s41398-018-0248-x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic basal forebrain neurons regulate fear extinction consolidation through p75 neurotrophin receptor signaling

Abstract: Cholinergic basal forebrain (cBF)-derived neurotransmission plays a crucial role in regulating neuronal function throughout the cortex, yet the mechanisms controlling cholinergic innervation to downstream targets have not been elucidated. Here we report that removing the p75 neurotrophin receptor (p75NTR) from cBF neurons induces a significant impairment in fear extinction consolidation. We demonstrate that this is achieved through alterations in synaptic connectivity and functional activity within the medial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
(59 reference statements)
2
17
0
1
Order By: Relevance
“…Despite this, the authors reported a ten-fold increase in synaptic connectivity between cBF neurons and target cells in the prefrontal cortex, an outcome that could be reversed by re-expression of p75 NTR in adult cBF neurons [79], thereby confirming a role for p75 NTR in pruning adult cBF connections. By contrast, synaptic connections to the dorsal hippocampus were relatively rare, and septo-hippocampal synaptogenesis was unaffected by manipulation of p75 NTR expression [79]. These observations indicate that p75 NTR controls presynaptic mechanisms of cBF synapse formation.…”
Section: Effects Of Loss Of P75 Ntr Expression On Cbf Morphologymentioning
confidence: 95%
See 3 more Smart Citations
“…Despite this, the authors reported a ten-fold increase in synaptic connectivity between cBF neurons and target cells in the prefrontal cortex, an outcome that could be reversed by re-expression of p75 NTR in adult cBF neurons [79], thereby confirming a role for p75 NTR in pruning adult cBF connections. By contrast, synaptic connections to the dorsal hippocampus were relatively rare, and septo-hippocampal synaptogenesis was unaffected by manipulation of p75 NTR expression [79]. These observations indicate that p75 NTR controls presynaptic mechanisms of cBF synapse formation.…”
Section: Effects Of Loss Of P75 Ntr Expression On Cbf Morphologymentioning
confidence: 95%
“…However, the increased cBF axonal density could also be due to the increased cBF neuronal number, rather than, or as well as, an increase in the size of individual neuronal arbors. Although this is difficult to accurately delineate, labelling of individual axonal arbors has revealed that the arbor size of MS/VDB cBF neurons innervating the hippocampus and prefrontal cortex is not substantially affected by the lack of p75 NTR cBF neuronal expression [79], suggesting that the previously reported increased innervation was due to the overlapping arbors of the additional surviving cBF neurons. Despite this, the authors reported a ten-fold increase in synaptic connectivity between cBF neurons and target cells in the prefrontal cortex, an outcome that could be reversed by re-expression of p75 NTR in adult cBF neurons [79], thereby confirming a role for p75 NTR in pruning adult cBF connections.…”
Section: Effects Of Loss Of P75 Ntr Expression On Cbf Morphologymentioning
confidence: 96%
See 2 more Smart Citations
“…cBF neuronal lesioning in a range of mouse AD models worsens many features of AD, including promoting cognitive impairment, and increasing Aβ accumulation, plaque load and inflammation (as observed herein), as well as causing tau hyperphosphorylation, hippocampal degeneration, and reduced BDNF expression (Gil-Bea et al, 2012;Ramos-Rodriguez et al, 2013;Hartig et al, 2014;Laursen et al, 2014;Turnbull et al, 2018). On the other hand, AD model rodents with increased cBF connectivity (Boskovic et al, 2014;Boskovic et al, 2018;Qian et al, 2018) or those which are treated with muscarinic receptor agonists display cognitive improvements and significantly reduced age-dependent A accumulation and inflammation compared to control rodents (Fisher et al, 2016). Cholinergic activation of muscarinic receptors also stimulates non-amyloidogenic APP processing (Rossner et al, 1998), thereby regulating the levels of Aβ in the interstitial fluid (Welt et al, 2015).…”
Section: Cbf Degeneration Is An Early Ad Feature That Can Drive Othermentioning
confidence: 55%